2018
DOI: 10.15632/jtam-pl.56.1.43
|View full text |Cite
|
Sign up to set email alerts
|

Reduced number of design parameters in optimum path synthesis with timing of four-bar linkage

Abstract: The paper presents the method for the optimal synthesis of four-link mechanism generating open/closed paths with time prescription. Although the method is suitable for both closed and open paths, it enables decreasing the number of design parameters describing dimensions, orientation and position of a path generator. Compared to the methods presented in the references, this is a one-phase synthesis method; although the number of design parameters is reduced, the method does not require affine transformations t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The asteroid is the desired trajectory for this example when uniformly sampled by 40 discrete points [6]. The parametric equation for this curve is defined as x t ð Þ = 5cos 3 (2pt), y t ð Þ = 5sin 3 (2pt), t = 0, 1 ½ .…”
Section: Example 3 (Asteroid)mentioning
confidence: 99%
See 2 more Smart Citations
“…The asteroid is the desired trajectory for this example when uniformly sampled by 40 discrete points [6]. The parametric equation for this curve is defined as x t ð Þ = 5cos 3 (2pt), y t ð Þ = 5sin 3 (2pt), t = 0, 1 ½ .…”
Section: Example 3 (Asteroid)mentioning
confidence: 99%
“…5 The solving methods for such problems in the literature can mainly vary based on the type of mechanism, the path geometry, the nature of the problem, etc. 6 The nature of the problem can be classified into two main categories: prescribed timing and non-prescribed timing problems. The term ''prescribed timing'' refers to a oneto-one correspondence between the input crank angle and each point of the desired trajectory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They applied the technique instead of traditional penalty functions and demonstrated that TLBO revealed the best performance. Bu skiewicz 41 introduced a one-step method for optimizing the open-path generation of the four-bar mechanism with timing. An objective function is defined to reduce the number of the design variables to six.…”
Section: Introductionmentioning
confidence: 99%
“…Bai et al (2020) studied a single-degree-of-freedom 10-bar mechanism to track 10 exact positions. Among the above three kinds of mechanism synthesis problems, the path generation of four-bar linkages is the most challenging problem (Wampler et al, 1992;Khan et al, 2015;Buskiewicz, 2018) because of the complexity of the path synthesis equation. To solve path synthesis equations, various methods were attempted, such as the homotopy method, the evolutionary algorithm, and the Fourier algorithm (Morgan and Wampler, 1990;Cabrera et al, 2011;Guigue and Hayes, 2016).…”
Section: Introductionmentioning
confidence: 99%